Does investing abroad reduce the ecological footprints at home? Analysis of outward GFDI and M&A from developed and developing countries - Ashraf, Ayesha (Archīum Ateneo, 2022)
This is the first study to estimate the effects of outward foreign direct investment (FDI) with its two modes of exit, outward greenfield FDI flows (GFDI) and cross-border mergers and acquisitions purchases (M&A), on four ecological footprints (EFs) of source (home) countries of FDI. We examine a global sample of 111 countries with the help of a dynamic panel estimator. We find that outward GFDI reduces the Consumption EF and Production EF of home countries irrespective of their level of development, confirming the reverse FDI ecological haven hypothesis, while M&A produces mixed results in developing countries. Additionally, the effects of both outward FDI types on Imports EF and Exports EF in developed countries are mostly positive, raising questions related to the management of the international production value chains and international cooperation for global protection of ecosystems. A stable planetary ecological system is critical for continuous human development. With the growing internationalization of production, the distribution of the ecological burden across countries is of enormous importance. Our study has implications for the protection of global ecosystems’ services, calling for a multinational agreement for preserving planetary ecological stability.